2005
DOI: 10.1175/mwr-2841.1
|View full text |Cite
|
Sign up to set email alerts
|

Spectral (Bin) Microphysics Coupled with a Mesoscale Model (MM5). Part II: Simulation of a CaPE Rain Event with a Squall Line

Abstract: Spectral (bin) microphysics (SBM) has been implemented into the three-dimensional fifth-generation Pennsylvania State University–NCAR Mesoscale Model (MM5). The new model was used to simulate a squall line that developed over Florida on 27 July 1991. It is shown that SBM reproduces precipitation rate, rain amounts, and location, radar reflectivity, and cloud structure much better than bulk parameterizations currently implemented in MM5. Sensitivity tests show the importance of (i) raindrop break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 28 publications
11
112
0
Order By: Relevance
“…Based on previous modeling studies [Lynn et al, 2005;Khain et al, 2005;van den Heever et al, 2006van den Heever et al, , 2011Rosenfeld et al, 2008;Storer et al, 2010;Storer and van den Heever, 2013;Fan et al, 2013], we would expect an increase in cloud ice with increased aerosol amounts. However, there is some uncertainty associated with the values of ice water path due to the fact that radar-based retrievals of ice water content are sensitive to the choice of the size and density parameters used [Protat et al, 2009].…”
Section: Shown Inmentioning
confidence: 98%
“…Based on previous modeling studies [Lynn et al, 2005;Khain et al, 2005;van den Heever et al, 2006van den Heever et al, , 2011Rosenfeld et al, 2008;Storer et al, 2010;Storer and van den Heever, 2013;Fan et al, 2013], we would expect an increase in cloud ice with increased aerosol amounts. However, there is some uncertainty associated with the values of ice water path due to the fact that radar-based retrievals of ice water content are sensitive to the choice of the size and density parameters used [Protat et al, 2009].…”
Section: Shown Inmentioning
confidence: 98%
“…Cui et al [2006] obtained similar results when studying an isolated cloud in an environment with low wind shear and with relatively dry air in the midtroposphere and upper troposphere. Lynn et al [2005aLynn et al [ , 2005b implemented the SBM into the three-dimensional fifth-generation Pennsylvania State University -National Center for Atmospheric Research (NCAR) Mesoscale Model (MM5) to simulate a squall line that developed over Florida. Their results demonstrated that the use of a continental CCN concentration resulted in an overall delay in the growth of hourly rainfall and formation of a stronger squall line with higher updraft maxima.…”
Section: à3mentioning
confidence: 99%
“…Most recently, a midweek increase in precipitation over U.S. has been suggested using the Tropical Rainfall Measuring Mission (TRMM) precipitation measurements and has been attributed to invigoration of rainstorms by air pollution [Bell et al, 2008]. Cloud simulations by Wang [2005], Lynn et al [2005b], Teller and Levin [2006], and Fan et al [2007aFan et al [ , 2007b support the possibility that in a moist, unstable atmosphere pollution aerosols can invigorate convective clouds and produce more precipitation. Khain et al [2005] showed that an increase in aerosol concentrations can both decrease and increase precipitation, depending on environmental conditions such as the relative humidity and dynamical factors, which can foster secondary cloud formation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, absorption of solar radiation by dust, results in heating of the dust layer and subsequently in modification of the thermodynamic and dynamical structure of the atmosphere, thus leading to suppression or enhancement of precipitation depending on the type of the clouds (Yin and Chen, 2007;Lau et al, 2009;Wilcox et al, 2010). The interplay between cloud dynamics and the composition of the atmosphere may delay the initiation of precipitation or steer a storm towards a different location and precipitation amounts will vary accordingly (Lynn et al, 2005b;van den Heever and Cotton, 2007;Rosenfeld at al., 2007;Zhang et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%